PENGARUH KEPUASAN KEJA, MOTIVASI KERJA DAN KOMITMEN ORGANISASIONAL TERHADAP KINERJA KARYAWAN: Studi Kasus Pada Karyawan ARENA PUB & RESTAURANT - Putu Krisda Pramitha Wiyani; Putu Bagus Suthanaya (Journal Research of Management, 2022)
Performance is the result of work that has a strong relationship with the organization's strategic goals, customer satisfaction, and contributes to the economy. Job satisfaction, work motivation and organizational commitment can affect employee performance. This study aims to examine the effect of job satisfaction, work motivation and organizational commitment on employee performance. Case study of Arena Pub & Restaurant employees. This research was conducted at Arena Pub & Restaurant Sanur. Determination of the sample using certain considerations. The number of respondents used in this study were 70 people. The research method used is quantitative research and for data analysis using multiple linear regression analysis. The results of the study stated that job satisfaction had a positive and significant effect on the performance of employees at Arena Pub & Restaurant with a significance value of 0.005 <0.05. Work motivation has a positive and significant effect on employee performance at Arena Pub & Restaurant with a significance value of 0.002 <0.05. Organizational commitment has a positive and significant effect on employee performance at Arena Pub & Restaurant with a significance value of 0.005 <0.05.